A Proteção do Direito à Habitação na Carta Social Europeia e no Direito Português - Afonso, Ana (2017)
This paper addresses the recognition of housing rights in the European Social Charter, considering, in particular the extent up to what do the legal measures and practices taken by the Portuguese State meet the European Social Charter requirements. Abstract: Este artigo analisa o direito à habitação reconhecido na Carta Social Europeia, considerando, em particular, até que ponto as políticas legislativas e medidas adotadas pelo Estado português cumprem os requisitos da Carta Social Europeia.